Studi Perbandingan Dampak Lingkungan Produksi Biogas Dari Bahan Baku Substrat Kotoran Sapi dan Sampah Organik Padat - Muhammad Ridha Rivaldi; Andri Saputra; Deni Swantomo (Universitas Batanghari Jambi, 2022)
One of the renewable energy sources that has the potential as a source of energy mix to support energy needs in Indonesia is biogas. Biogas production by means of an anaerobic digester can be carried out with various types of substrates, including cow dung and organic solid waste. In carrying out a production, it is necessary to pay attention to the aspects that are caused to the environment. Life Cycle Assessment (LCA) can be used as a method of assessing the environmental impact of a product. The purpose of this study was to determine the environmental impact of biogas production activities from cow dung substrate and solid organic waste. LCA research was conducted using OpenLCA software version 1.10 with a functional unit based on the energy needs of the people of Yogyakarta at 41.554,342 kWh/hour. This study applies cradle to gate limits covering sources, transportation, production, and the resulting waste. The results showed that biogas production made from cow dung substrate had a lower environmental impact than biogas production made from solid organic waste. The most dominant environmental impact of the two biogas productions is eutrification, with a contribution of 2,12x105 kg PO4-eq (cow dung substrate) and 9,80x105 kg PO4-eq (solid organic waste). Process stages in biogas production that contribute dominantly to environmental pollution include transportation activities and by-products of liquid waste and sludge. The interpretation results produce several recommendations for improvement analysis, including substitution of fuel oil into compressed natural gas type gas fuel, processing of fermented sludge waste into fertilizer, processing of liquid waste with the plasma dielectric barrier discharge method.